Our songs and other people's songs : music and identities in a lutheran diocese in Tanzania - Lampinen, Leena (Taideyliopiston Sibelius-Akatemia, DocMus-tohtorikoulu, 2021)
In the Evangelical Lutheran Church in Tanzania (ELCT), singing in a choir is a popular activity, and there are many choirs of different kinds within its parishes. In this study, the focus is on church choirs and choir conductors (walimu wa kwaya) within the North Central Diocese of the ELCT in the northern part of Tanzania. The central question of this research is: In what ways are choral repertoires involved in the formation of diverse identities within church choirs in a Lutheran diocese in Tanzania? The main theoretical concept employed in this study is that of identity, which I approach from individual, social, and group aspects. In addition to the differentiation between individual, social, and group, identities can be further labeled according to the context to which they are related, which in this study includes religious, ethnic, and national viewpoints. All the aforementioned sides of identity are related to music sung by church choirs of the North Central Diocese. Methodologically, I have combined several approaches. The main focus was on thematic interviews with ten choir conductors. A larger group – 105 choir conductors – participated in the study through a written survey that contributed especially to the creation of a framework and a basic understanding of the context in which the participants of this study function. In addition, this work contains ethnographic features. In this research, religious worldview and the church context form the basis for choirs’ activities. The choirs also define themselves by choosing a certain way of functioning, including musical and organizational choices. Repetition and routines are important factors in creating cohesiveness within choirs and are accentuated in this context, in which choirs gather for rehearsals several times a week and participate in worship service every Sunday. Sunday services and choirs’ various roles within them are important occasions for shaping the choirs’ self-understanding. Choirs see themselves as active agents: they are conveying the Christian message and supporting congregational singing. At the individual level, the research participants identified themselves in several ways. The interviewees saw themselves as choir conductors, music teachers, composers, singers, performers of certain musical styles, representatives of particular ethnic groups, and/or members of a religious community. Musical collaboration is an important feature in the work of walimu, which offers a means for expanding musical resources. It is also a source for the feeling of belonging and collegiality, both within the ELCT and ecumenically with walimu from other denominations. The selection of choral repertoire is a process through which walimu and other people involved in repertoire-related decisions influence the image that a choir presents of itself. It is a way of defining who they are, who they are not, and/or who they would like to be. On the other hand, the identity of a choir influences the repertoire selection. In this study, the choral repertoires consist of old and new materials, local and global influences, our songs and other people’s songs, and they are intersections of personal, group, musical, religious, local, and ethnic identities.

Kuorolaulu on suosittu toimintamuoto Tansanian evankelisluterilaisessa kirkossa, ja monenlaisia kuoroja on paljon. Tutkimukseni keskittyy yhden luterilaisen hiippakunnan (North Central Diocese) kuoroihin ja kuoronjohtajiin (walimu wa kwaya) Tansanian pohjoisosassa. Tutkimuksen pääkysymys on: Millä tavoin kuorojen ohjelmistot ovat mukana erilaisten identiteettien rakentumisessa yhden tansanialaisen luterilaisen hiippakunnan kuorojen keskuudessa? Tärkein tässä tutkimuksessa käytetty teoreettinen käsite on identiteetti, jota lähestyn sekä yksilön (henkilökohtainen ja sosiaalinen identiteetti) että ryhmän näkökulmasta. Identiteettejä voidaan myös jaotella sen mukaan, mihin kontekstiin ne liittyvät. Tässä tutkimuksessa näihin kuuluvat uskonnollinen, etninen ja kansallinen identiteetti. Kaikki edellä mainitut näkökulmat liittyvät tavalla tai toisella musiikkiin, jota tutkimuksessa käsitellyt kuorot laulavat. Käytän työssäni useita metodologisia lähestymistapoja. Keskiössä ovat kymmenen kuoronjohtajan kanssa tehdyt teemahaastattelut. Laajempi joukko kuoronjohtajia – 105 henkilöä – osallistui kyselytutkimukseen, jonka tärkeimpänä tavoitteena oli luoda kokonaiskuvaa kontekstista, jossa tutkimukseen osallistujat toimivat. Työni sisältää myös etnografisia piirteitä. Tässä tutkimuksessa uskonnollinen maailmankatsomus ja kirkollinen konteksti luovat pohjan kuorojen toiminnalle. Kuorot määrittelevät itseään myös tekemällä esimerkiksi musiikillisia tai organisaation rakenteeseen liittyviä valintoja. Toistuvuus ja rutiinit ovat tärkeitä tekijöitä kuorojen yhteenkuuluvuuden tunteen luojina. Ne korostuvat tässä ympäristössä, jossa kuorot kokoontuvat harjoituksiin useita kertoja viikossa ja osallistuvat jumalanpalvelukseen joka sunnuntai. Jumalanpalvelukset ja kuorojen monet roolit niissä ovat tärkeitä tilanteita kuorojen itseymmärryksen muotoutumiselle. Kuorot näkevät itsensä aktiivisina toimijoina: ne välittävät kristillistä sanomaa ja tukevat seurakuntalaulua. Yksilötasolla osallistujat identifioivat itsensä monin tavoin. He olivat kuoronjohtajia, musiikinopettajia, säveltäjiä, laulajia, tietyn musiikkityylin esittäjiä, etnisen ryhmän edustajia ja/tai uskonnollisen yhteisön jäseniä. Yksi tärkeä piirre kuoronjohtajien työssä on musiikillinen yhteistyö, joka mahdollistaa musiikillisten resurssien laajentumisen. Yhteistyö luo yhteenkuuluvuuden ja kollegiaalisuuden tunnetta sekä luterilaisen kirkon sisällä että ekumeenisesti muiden kirkkokuntien kuoronjohtajien kanssa. Kuoro-ohjelmiston valikoituminen on prosessi, jonka kautta kuoronjohtajat ja muut ohjelmistoon liittyvässä päätöksenteossa mukana olevat vaikuttavat kuoron itsestään antamaan kuvaan. Se on keino määritellä ketä he ovat tai eivät ole, ja/tai ketä haluaisivat olla. Toisaalta taas kuoron identiteetti vaikuttaa ohjelmiston valintaan. Tässä tutkimuksessa kuoro-ohjelmistot koostuvat vanhasta ja uudesta materiaalista, paikallisista ja globaaleista vaikutteista, meidän ja muiden lauluista, ja ne ovat yksilö- ja ryhmäidentiteettien sekä musiikillisten, uskonnollisten, paikallisten ja etnisten identiteettien kohtaamispaikkoja.
Keywords: Tansania; kuorot; kuoronjohtajat; ryhmäidentiteetti; ohjelmistot; luterilaiset kirkot